Hematopoietic Origin of Murine Lung Fibroblasts - Lindsay T. McDonald; Meenal Mehrotra; Amanda C. LaRue (Stem Cells International)
Multiple origins, including the bone marrow, have been suggested to contribute to fibroblast populations in the lung. Using bone marrow reconstitution strategies, the present study tested the hypothesis that the bone marrow hematopoietic stem cell (HSC) gives rise to lung tissue fibroblasts in vivo. Data demonstrate that the nonadherent bone marrow fraction is enriched for CD45+ HSC-derived cells and was able to reconstitute hematopoiesis in lethally irradiated animals. Analysis of peripheral blood and lung tissues from engrafted mice demonstrated the ability of this population to give rise to CD45+/Discoidin-Domain Receptor-2+ (DDR2) circulating fibroblast precursors (CFPs) in blood and fibroblast populations in lung. An HSC origin for lung fibroblasts was confirmed using a novel clonal cell transplantation method in which the bone marrow is reconstituted by a clonal population derived from a single HSC. Together, these findings provide evidence for an HSC contribution to lung fibroblasts and demonstrate a circulating intermediate through the CD45+/DDR2+ HSC-derived CFP.